Analysis of the 5th-Grade Student and Teacher’s Needs Based on Learning Style in Emancipated Curriculum to Develop Differentiated Assessment - Ni Wayan Surya Mahayanti; Luh Gd Rahayu Budiarta; Ni Putu Deliana Mentari (Journal of English Language Learning, 2024)
This research aims to analyze the needs of grade 5 elementary school students and teachers based on learning styles in the emancipated curriculum to develop differentiated assessments. This research took place in Buleleng with 27 students and one teacher as respondents. Using the descriptive qualitative method, the data was collected through direct observation, interviews, open-ended questionnaires using the VARK Fleming (2001) model, and English textbook analysis. The results of the analysis of interviews with teachers showed the conclusion that the implementation of the curriculum had not yet been optimal and is still in the adjustment stage; therefore, the learning and assessment process is not yet differentiated. The analysis of student questionnaires shows that there are different student learning styles, with the visual learning style being the most dominant, received 143 answers. With these results, teachers can modify learning media and activities to meet each student's needs and learning styles.